Pengaruh Efektivitas Proses Bisnis dan Komitmen Organisasi Terhadap Kualitas Sistem Informasi Akuntansi (Survei Pada Perusahaan Asuransi Umum di Kota Bandung) - Samuel Gautama Abidin; yenni carolina (Magister Akuntansi FB-UK.Maranatha, 2021)
In a few decades, there is a lot of changes in many field that happened because of technological development, one of them is a changes in the working system by Informational Technology (IT). A spesific form of working system is Accounting Information System (AIS) that can be distribute financial information to all of stakeholders. Recently, a companies in the midst of an increasingly widespread global competition are required to respond any changes and continue to improve their competitive advantage with their technologies, in specific case the insurance companies (both life insurance and general insurance) are challenged to implement the information technology and information systems (included AIS) to be able to compete in the global economical market. This competitive advantage can be reached by the existence of an corporate AIS quality. AIS can be influenced by various factors, included the business process effectiveness that implemented by the firm and the organizational commitment that attached to firm’s employees. This research aims to measure business process effectiveness and organizational commitment influence to AIS quality partially and simultaneusly. This research use sample data that collected by convenience sampling method with questionnaires that contain assessment statements with differential scales. The sample of this research was 78 employees who worked for eight general insurance firm in Bandung, West Java. Several conclusions were obtained from the four hypotheses. First, there is a different between average value of business process effectiveness and the average value of organizational commitment. Second, the business process effectiveness is proven to affect the AIS quality partially by 62,25%. Third, the organizational commitment is proven to affect the AIS quality partially by 64,48%. Fourth, the business process effectiveness and organizational commitment are proven to affect the AIS quality simultaneously by 70,90%.